Syncope in association with Prinzmetal variant angina. Issue 7 (July 1975) - Harper, R; Peter, T; Hunt, D
Abstract : A case of Prinzmetal variant angina with transient complete atrioventricular block and syncopal episodes following an anteroseptal myocardial infarction is described. The syncopal attacks were not prevented by demand cardiac pacing and were presumably caused by transient severe ischaemia of the left ventricle, with a consequent reduction in cardiac output. The left ventriculogram showed a large anterior dyskinetic area corresponding to the high grade proximal obstruction in the left anterior descending artery demonstrated by coronary angiography. All other coronary vessels appeared free of disease and it is suggested that the anginal episodes were caused by transient proximal segmental spasm of the right coronary artery. The anginal episodes were successfully prevented by a regimen of two-hourly coronary arterial vasodilator therapy.